Respostas

2014-05-05T22:04:58-03:00
y= 7^{x}

y= ( \frac{1}{7} )^{x+1}

a) y=1

y= 7^{x}1= 7^{x}7^{0} = 7^{x}x=0

y= ( \frac{1}{7} )^{x+1}1= ( \frac{1}{7} )^{x+1}( \frac{1}{7} )^{0}= ( \frac{1}{7} )^{x+1}x+1=0x=-1


b) y=343= 7^{3}

7^{3} = 7^{x}x=3

7^{3} = ( \frac{1}{7} )^{x+1}7^{3} = ( 7 )^{-x-1}-x-1=3-x=4x=-4


c) y= \sqrt[5]{ 7^{4} } = 7^{ \frac{4}{5} }

7^{ \frac{4}{5} } = 7^{x}x= \frac{4}{5}

7^{ \frac{4}{5} } = ( \frac{1}{7} )^{x+1}7^{ \frac{4}{5} } = ( 7)^{-x-1}-x-1= \frac{4}{5} -x= \frac{4}{5} +1-x= \frac{9}{5}x= -\frac{9}{5}